2022
DOI: 10.24815/jpsi.v10i3.24153
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship of Self-Efficacy Towards High Level of Thinking Ability of USK Physics Education Student in Basic Physics I Course

Abstract: The high-order thinking ability of students is currently a problem that is so difficult to improve because it must be extra developed in teaching and learning activities. This can happen because students do not often improve their higher order thinking in everyday life and in the learning process. Most students tend to have difficulty solving problems when the lecturer gives problems with a higher level of difficulty than usual. The cause of this problem needs to be investigated. This study aims to determine t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…The results of this analysis are by previous research that there is a positive relationship between self-efficacy and HOTS, but it does not have a significant effect. This is because previous studies' results have moderate self-efficacy levels but tend to have less or low HOTS levels (Afdar & Zakaria, 2022).…”
Section: Figure 1 Sobel Test Resultsmentioning
confidence: 97%
“…The results of this analysis are by previous research that there is a positive relationship between self-efficacy and HOTS, but it does not have a significant effect. This is because previous studies' results have moderate self-efficacy levels but tend to have less or low HOTS levels (Afdar & Zakaria, 2022).…”
Section: Figure 1 Sobel Test Resultsmentioning
confidence: 97%
“…Zahodne et al (2015) indicated that personal efficacy beliefs can enhance cognitive performance through cognitive, emotional, and motivational processes [90]. General self-efficacy is associated with critical thinking awareness as part of higher-order thinking [91] because individuals need to have confidence in their own abilities to solve problems, make decisions, etc. [34].…”
Section: Research Hypothesismentioning
confidence: 99%
“…Self-efficacy can boost students' comfort and confidence when participating in classroom discussions (Amin, 2022b). Self-efficacy can affect students' self-regulation such as goal setting, thinking skills, and self-assessment (Nurulwati et al, 2022). Science process skills are an important element that plays a role in stimulating critical thinking skills (Darmaji et al, 2021).…”
Section: 027 Hypothesis Acceptedmentioning
confidence: 99%